Early Innovation Adoption: Effects of Performance-Based Motivation and Organizational Characteristics - Yun, Changgeun (Public Performance and Management Review, 2020)
Early adopters of innovation play a critical role in the successful spread of the innovation by legitimizing the adoption of the innovation and/or providing evidence of its effectiveness. This article explores why some organizations adopt innovations before than others by focusing on determinants of early innovation adoption. Analysis reveals that there is a U-shaped influence of organizational performance on early innovation adoption. Most organizations are encouraged to be early adopters by their poor performance, but some organizations with very high performance tend to be innovation-friendly. Other organizational characteristics such as organizational size and pro-innovation bias also have positive impacts on early innovation adoption. These findings have practical implications about strategies for successfully diffusing innovations.
Keywords: Direct experience; early innovation adoption; organizational size; performance-based motivation; pro-innovation bias